Trends in direct oral anticoagulant (DOAC) prescribing in English primary care (2014-2019) - Joy, M; Williams, J; Emanuel, S; Kar, D; Fan, X; Delanerolle, G; Field, BCT; Heiss, C; Pollock, KG; Sandler, B; Arora, J; Sheppard, JP; et al. (BMJ Publishing Group, 2022)
Background: In England, most prescribing of direct-acting oral anticoagulants for atrial fibrillation (AF) is in primary care. However, there remain gaps in our understanding of dosage and disparities in use. We aimed to describe trends in direct oral anticoagulant (DOAC) prescribing, including dose reduction in people with renal impairment and other criteria, and adherence. Methods: Using English primary care sentinel network data from 2014 to 2019, we assessed appropriate DOAC dose adjustment with creatinine clearance (CrCl). Our primary care sentinel cohort was a subset of 722 general practices, with 6.46 million currently registered patients at the time of this study. Results: Of 6 464 129 people in the cohort, 2.3% were aged ≥18 years with a diagnosis of AF, and 30.8% of these were prescribed vitamin K antagonist and 69.1% DOACs. Appropriate DOAC prescribing following CrCl measures improved between 2014 and 2019; dabigatran from 21.3% (95% CI 15.1% to 28.8%) to 48.7% (95% CI 45.0% to 52.4%); rivaroxaban from 22.1% (95% CI 16.7% to 28.4%) to 49.9% (95% CI 48.5% to 53.3%); edoxaban from 10.0% (95% CI 0.3% to 44.5%) in 2016 to 57.6% (95% CI 54.5% to 60.7%) in 2019; apixaban from 30.8% (95% CI 9.1% to 61.4%) in 2015 to 60.5% (95% CI 57.8% to 63.2%) in 2019. Adherence was highest for factor Xa inhibitors, increasing from 50.1% (95% CI 47.7% to 52.4%) in 2014 to 57.8% (95% CI 57.4% to 58.2%) in 2019. Asian and black/mixed ethnicity was associated with non-adherence (OR 1.81, 95% CI 1.56 to 2.09) as was male gender (OR 1.19, 95% CI 1.15 to 1.22), higher socioeconomic status (OR 1.60, 95% CI 1.52 to 1.68), being an ex-smoker (OR 1.12, 95% CI 1.06 to 1.19) and hypertension (OR 1.07, 95% CI 1.03 to 1.17). Conclusions: The volume and quality of DOAC prescribing has increased yearly. Future interventions to augment quality of anticoagulant management should target disparities in adherence.